Influence Leadership, Motivation Employees, and Work Enthusiasm on Employee Performance - Rostina, Cut Fitri; Alua, Awu Arnol; Hura, Andi Krisman; Fauzi, Fauzi (Lembaga Riset Ilmiah, 2023)
Human resource management is a process consisting of planning, organizing, leading, and controlling activities related to job analysis, job evaluation, procurement, development, compensation, promotion, and termination of employment in order to achieve the stated goals. The purpose of this study was to determine the influence of leadership, motivation, and morale on employee performance in the Medan Selayang District Office, Medan City. The data analysis technique in this study used multiple linear regression analysis. With a sample of 83 employees. And the results of the study show that leadership and motivation have no effect on employee performance but are different from work enthusiasm which has a significant effect on employee performance